Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Membayar Zakat di Masyarakat - Syukrillah, Zaenal; Zen, Muhammad (FDIK IAIN Padangsidimpuan, 2024)
AbstractZakat is an obligation for Muslims who can afford it. Compliance in paying zakat is still an important issue in Indonesia. This research aims to analyze the factors that influence compliance with paying zakat in society. The research method used is literature analysis by examining various sources such as scientific journals, books and related articles. The results of the analysis show that the adequacy of paying zakat is influenced by various factors, both internal and external. Internal factors include faith, understanding of religion, knowledge of zakat, intrinsic motivation, and social concern. External factors include income, social environment, ease of access to zakat institutions, trust in zakat institutions, and effectiveness of zakat socialization. Increasing compliance with paying zakat can be done through various efforts, such as increasing religious understanding regarding zakat, developing zakat education programs, increasing transparency of zakat institutions, creating a conducive social environment, and developing effective zakat socialization strategies.Keywords: Compliance with Paying Zakat, Internal Factors, External Factors, Intrinsic Motivation, Zakat Socialization.